2021
DOI: 10.2174/1386207323666200914103719
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of the Mechanisms of Mulberry Leaf (Morus alba Linne) Acting on Diabetes Based on Network Pharmacology and Molecular Docking

Abstract: Background: Diabetes mellitus is one of the most common endocrine metabolic disorder diseases. The application of herbal medicine to control glucose levels and improve insulin action might be a useful approach in the treatment of diabetes. Mulberry leaves (ML) has been reported to exert important activities of anti-diabetic. Objective: In this work, we aimed to explore the multi-targets and multi-pathways regulatory molecular mechanism of Mulberry leaves (ML, Morus alba Linne) acting on diabetes. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previous evidence has indicated that miR-98-5p affects apoptosis, inflammation and oxidative stress by regulating the PI3K/Akt signaling pathway (27)(28)(29). Moreover, studies have shown that IGF1R can affect the development of diabetes through the PI3K/Akt/eNOS axis (30)(31)(32).…”
Section: Protective Effects Of Endothelial Progenitor Cell Microvesic...mentioning
confidence: 99%
“…Previous evidence has indicated that miR-98-5p affects apoptosis, inflammation and oxidative stress by regulating the PI3K/Akt signaling pathway (27)(28)(29). Moreover, studies have shown that IGF1R can affect the development of diabetes through the PI3K/Akt/eNOS axis (30)(31)(32).…”
Section: Protective Effects Of Endothelial Progenitor Cell Microvesic...mentioning
confidence: 99%
“…Moreover, IL-6 and TNF were inflammatory factors involved in the process of inflammatory response. The production of cytokines such as IL-6 is induced by TNF and is involved in inflammatory responses and oxidative stress processes ( 11 , 12 ). The C-type lectin receptor signaling pathway plays an important role in host fungal infection by coordinating the immune system against infection ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Docking study on (4Z, 12Z)-cyclopentadeca- 9) isolated from Grewia hirsuta against target protein GSK-3 has shown that the oxygen atom of the isolated compound reacts with LYS-85 residue of GSK-3 and forms hydrogen bond through a strong hydrophobic interaction [154]. Quercetin ( 22) (Figure 6), iristectorigenin A (38), 4-prenylresveratrol (39), moracin H (40), moracin C (41), isoramanone (42), moracin E (43), and moracin D (44) (Figure 10) isolated from leaves of Morus alba Linne have shown good affinity to AKT-1 target protein [155]. Molecular docking and SAR studies conducted on compounds of different chemical categories are also reported, and these data could be useful in predicting activities of natural compounds with related structures.…”
Section: Discussionmentioning
confidence: 99%